2012
DOI: 10.1074/jbc.m112.384875
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Heparan Sulfate 6-O-Sulfation Levels Regulate Angiogenic Responses of Endothelial Cells to Fibroblast Growth Factor 2 and Vascular Endothelial Growth Factor

Abstract: Background: Heparan sulfate (HS) is an essential regulator of multiple angiogenic growth factors. Results: Down-regulation of 6-O-sulfation in endothelial cell HS affects FGF2-and VEGF-mediated endothelial cell functions. Conclusion:The level of 6-O-sulfation in specific HS domains regulates endothelial cell responses to angiogenic growth factors. Significance: The relationships between 6-O-sulfation and endothelial phenotypes could help to design HS sequences inhibiting angiogenic growth factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 39 publications
(42 reference statements)
1
66
0
Order By: Relevance
“…Our previous study demonstrated that ovarian high grade serous carcinomas have high levels of 6-O-sulfation in tumor endothelium when compared with the vasculature of normal ovarian tissue (26). We also found through down-regulation of HS6ST-1 or HS6ST-2 in endothelial cells that sulfation at the glucosamine 6-O position was critical for endothelial cell functions in vitro and in vivo (26).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous study demonstrated that ovarian high grade serous carcinomas have high levels of 6-O-sulfation in tumor endothelium when compared with the vasculature of normal ovarian tissue (26). We also found through down-regulation of HS6ST-1 or HS6ST-2 in endothelial cells that sulfation at the glucosamine 6-O position was critical for endothelial cell functions in vitro and in vivo (26).…”
mentioning
confidence: 95%
“…retro.puro plasmid (Origene) were described in the supplemental data of our previously published study (26). Two rounds of 24-h infection were performed as described (26), after which cells were cultured in the media containing 2 g/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations